The Haemus Mountains as a shelter, an attack outpost and an observation post in the light of the Bulgarian-Byzantine military relations in the early Middle Ages - Marinow, Kirył (Balcanica Posnaniensia. Acta et studia, 2013)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">After the analysis of sources (coming mainly from the period of the 8th–9th centuries), the author of the article claims that still from the outset of the khanate on the lower Danube, Bulgarians made the Haemus Mountains (Stara Planina and Sredna Gora) a permanent protective barrier from behind which they could launch their attacks against the territory of Byzantine Thrace. The mountains functioned as an attack outpost (680/681, 763 and 792) and a convenient observation post, which was used to monitor the Byzantine military stationed both at the northern as well as southern foot of the range (708, 763, 811). The mountains were also used as a shelter to which the defeated Bulgarian troops would retreat (763, 811).